PEMBELAJARAN DARING MATERI MENULIS TEKS NEGOSIASI PADA SISWA KELAS X DENGAN MENGGUNAKAN METODE DISCOVERY LEARNING - Fadilah, Lismayanti; Mustika, R. Ika; Ismayani, R. Mekar (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This reasearch was motivated by the researcher’s curiosity about the application of the method of discovery learning in online learning, especially in writing negotiation text in class X. The formulation of the problem of this study is how the results and responses of students to the application of discovery learning method in class X negotiation text material? The purpose of this study was to examine the results and responses of students to the application of the discovery learning method of writing negotiation text in class X. The research method used was descriptive qualitative. The sample used in this study were 33 students of class X IBB SMAN 1 Batujajar. The instruments used in this study were knowledge tests, skills tests and student quitionnaires. The results showed that the knowledge test based on the group was categorized as very good with an average value of 88,84. The knowledge test based on the individual was categorized as good with an average value of 75,90. The individual-based skill test was categorized as good with an average of 83,93. The The results of the student questionnaire with a total score of 1.949 were categorized as good with a percentage of 82,028%. So, it can be concluded that the discovery learning method is suitable for online learning in class X negotiation text material.